2021
DOI: 10.1177/01939459211055773
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Family Caregivers of People with Dementia during the COVID-19 Pandemic

Abstract: Although behavioral and psychological symptoms are burdensome for people with dementia and their caregivers, perceptions of family caregivers regarding management of these symptoms are unclear. This study explored the experiences of family caregivers regarding behavioral and psychological symptoms experienced by relatives with dementia, management of these symptoms, and changes in their experiences during the COVID-19 pandemic. A qualitative, exploratory approach using constant comparative methods was used; 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Increased carer stress, fatigue and burn-out has also been found in other studies 3 14 15. In one study 21 family carers, severe loneliness, and an overwhelming sense of loss and concern about worsening cognition in the person with dementia was identified 16. Concern about cognition and the impact of restrictions on cognition and neuropsychiatric symptoms has been identified more widely 17 18.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Increased carer stress, fatigue and burn-out has also been found in other studies 3 14 15. In one study 21 family carers, severe loneliness, and an overwhelming sense of loss and concern about worsening cognition in the person with dementia was identified 16. Concern about cognition and the impact of restrictions on cognition and neuropsychiatric symptoms has been identified more widely 17 18.…”
Section: Introductionmentioning
confidence: 72%
“… 3 14 15 In one study 21 family carers, severe loneliness, and an overwhelming sense of loss and concern about worsening cognition in the person with dementia was identified. 16 Concern about cognition and the impact of restrictions on cognition and neuropsychiatric symptoms has been identified more widely. 17 18 For example, one spanish study identified an increase in neuropsychiatric symptoms in people with Alzheimer’s Disease and Mild-Cognitive impairment during 5 weeks of lockdown, with agitation, apathy and aberrant motor behaviour being most prominent.…”
Section: Introductionmentioning
confidence: 99%
“…For caregivers of long-term patients, the changes may mean intensifying the hardship of caregiving on their existing conditions of their wellbeing. An inevitable surge of studies cropped up in the literature amidst the pandemic examining the kinds of problems and challenges faced by the caregivers of patients with life-long conditions (for example, dementia - Harris & Titler, 2021;Rainero, Bruni, Marra, Cagnin, Bonanni, Cupidi et al, 2021;cancer -Zeng, Cao, Zhao, Li, & Hou, 2021). Anderson and colleagues (2021) conducted a study with 604 family caregivers in the province of Alberta, Canada reported that the pandemic had affected the participants' emotional stability and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated the feasibility and acceptability of 1 potential tool for the toolkit prototype. The first author also conducted semistructured virtual interviews with 21 family caregivers and 2 focus groups with 7 PLWD to explore their experiences during the COVID-19 pandemic [ 29 ]. Findings showed a substantial need for in-home care strategies to manage stress among PLWD and care partners, specifically strategies not reliant on in-person training or interaction with people outside the home.…”
Section: Introductionmentioning
confidence: 99%